Reduction of Opioid Consumption After Outpatient Orthopaedic Trauma Surgeries Using a Multimodal Pain Protocol. Issue 3 (1st February 2022) - Siow, Matthew Y.; Mitchell, Brendon C.; Vuong, Carrie L.; Zanzucchi, Audrey; Finneran, John J.; Girard, Paul J.; Schwartz, Alexandra K.; Kent, William T.
Abstract : Introduction: Because of the dearth of literature in the orthopaedic trauma population, we aimed to analyze how a multimodal pain protocol after outpatient surgery affects opioid consumption, pain scores, and patient satisfaction. Methods: This was a cohort study with a historical control at an urban level 1 trauma center. Forty consecutive outpatients were given a peripheral nerve block and a multimodal pain protocol between September 2019 and March 2020 and compared with 70 consecutive preprotocol patients who received a peripheral nerve block and hydrocodone-acetaminophen. The primary outcome was morphine milligram equivalents (MMEs) consumed. Our secondary aims were pain scores and satisfaction. Results: Patients in the protocol were younger (36.45 versus 45.09 years, P = 0.007), butthere was no difference in sex, body mass index, American Society of Anesthesiologists, or surgical duration. There was a 59% reduction in opioids consumed in the first 4 days after surgery (3.83 MME versus 9.29 MME, P < 0.001). At the postoperative day-14 time point, protocol patients consumed a total of 5.59 MMEs, which is 40% less than just the first 4 days of the preprotocol ( P = 0.02). Protocol patients assigned a higher rating of "least pain" on postoperative day 1 (1.24 versus 0.52, P = 0.04) but had higher satisfaction scores on day 1 (9.68 versus 8.54, P < 0.001) and day 2 (9.66 versus 8.61, P < 0.001). Conclusion: Implementation of a multimodal pain management protocol after outpatient orthopaedic trauma surgeries reduced opioid consumption by >50% in the first 4 days postoperatively. Additional studies are needed to refine the multimodal pain protocol used in this study. Level of Evidence: II